The Academic Management Applied at Pesantren Musthafawiyah and its Implication in Enhancing Students’ Achievement and School Existence - Irma Suryani Siregar; Muh Misdar (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aimed to examine the implications of the academic management of Pesantren Musthafawiyah in improving santri achievement and the existence of the pesantren. Given that Pesantren Musthafawiyah is the oldest pesantren on the island of Sumatra, which was established in 1912, and in its history, the pesantren has experienced many challenges in its academic management. The research method used was a qualitative method with a descriptive analysis approach. Data were collected through observation, in-depth interviews, with the Miles and Huberman model as the data analysis technique. The results showed that the academic management of Pesantren Musthafawiyah had positive implications for students’ achievement both in the academic and non-academic fields. In addition to the academic management of Pesantren Musthafawiyah, it was able to provide positive implications for the existence of the pesantren, the preference of students and parents of students as well as the general public towards Pesantren Musthafawiyah, which viewed Pesantren Musthafawiyah as having excellent, full of achievement, charismatic, popular, having exemplary alumni and consistent in its education system.